Galloyl benzamide‐based compounds modulating tumour necrosis factor α‐stimulated c‐Jun N‐terminal kinase and p38 mitogen‐activated protein kinase signalling pathways. (16th June 2015) - Leo, Valentina; Stefanachi, Angela; Nacci, Carmela; Leonetti, Francesco; de Candia, Modesto; Carotti, Angelo; Altomare, Cosimo D.; Montagnani, Monica; Cellamare, Saverio
Abstract Objectives The aim of this work is to investigate whether and how two newly synthesized 3, 4, 5‐trimethoxygalloyl‐containing compounds 1 and 3 interfere with the mitogen‐activated protein kinase (MAPK) signalling pathways involved in several pathological events, ranging from inflammatory diseases to cancer. Methods The effects on the phosphorylation of MAP kinases (c‐Jun N‐terminal kinases (JNKs), p38) and activation of nuclear factor‐kappa B (NF‐κB) pathways of 1 and its 1H‐indazole‐containing analogue 3, compared with those elicited by the known Adenosine Triphosphate (ATP)‐competitive JNK inhibitor SP600125, were evaluated through Western blot analysis in murine fibroblasts NIH‐3T3 and human endothelial cells EA.hy926 acutely treated with tumour necrosis factor‐α (TNF‐α). Their effects on cell viability were also assessed by 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyltetrazolium bromide (MTT) assay. Key findings In cultured murine fibroblasts, 1 inhibited JNK signalling with a different mechanism from SP600125. It reduced c‐Jun phosphorylation without altering phosphorylation levels of JNK protein. Compound 3, showing a profile similar to SP600125, inhibited JNK phosphorylation and partially inhibited p38 MAPK at 50 μm concentration. Compound 3 and SP600125 showed similar behaviour in both cell cultures. In contrast, compound 1 in EA.hy926 cells significantly interfered with JNK phosphorylation, did not decrease phosphorylation of c‐Jun (Ser73), whereas significantly suppressed phosphorylation of p38 MAPK and reversed degradation of NF‐κB signalling components. Conclusions 3, 4, 5‐Trimethoxygalloyl‐based compounds 1 and 3, which did not show significant cell toxicity, modulate the TNF‐α‐induced activation of MAPK signalling, mainly inhibiting phosphorylation of JNK, c‐Jun and p38 MAPK, in murine fibroblasts and human endothelial cells with different MAPK selectivity profiles. These compounds deserve future investigation in specific cell‐based disease models and in‐vivo pharmacology.